2020
DOI: 10.1364/oe.392230
|View full text |Cite
|
Sign up to set email alerts
|

Absorption enhancement in all-semiconductor plasmonic cavity integrated THz quantum well infrared photodetectors

Abstract: The light coupling properties of all-semiconductor plasmonic cavity integrated THz quantum well infrared photodetectors were studied for absorption enhancement of the quantum wells. The all-semiconductor plasmonic cavity is constructed by heavily doped GaAs with a plasmonic behavior in the THz regime. The plasmonic behavior of GaAs was thoroughly studied by taking into account the carrier density dependent effective mass of electrons. An optimal doping level for GaAs to be the most metallic is selected since t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…The multiple-reflection interference is analyzed in detail later. Further, the circular polarization discrimination is magnified by the double polarization selection provided by the chiral metamirror and the QWs [ 19 , 40 , 45 ]. Since the QWs only absorb the light with a z-component electric field, the SPP wave excited by the RCP is efficiently absorbed by the QWs, while the LCP light directly incident on the QWs and that diffracted or scattered into the QWs is hardly absorbed, leading to CPER magnification.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The multiple-reflection interference is analyzed in detail later. Further, the circular polarization discrimination is magnified by the double polarization selection provided by the chiral metamirror and the QWs [ 19 , 40 , 45 ]. Since the QWs only absorb the light with a z-component electric field, the SPP wave excited by the RCP is efficiently absorbed by the QWs, while the LCP light directly incident on the QWs and that diffracted or scattered into the QWs is hardly absorbed, leading to CPER magnification.…”
Section: Resultsmentioning
confidence: 99%
“…When the spacer is replaced by a detection material, a prominent circular-polarization-discriminative absorption in the detection material is achieved. However, the ohmic loss of the metal parts impedes light absorption in the detection materials, although an impedance matching condition could be reached by tuning the thickness of the detection material [ 39 , 41 , 42 , 43 , 44 , 45 ]. We recently revealed that integrating an anisotropic detection material with a chiral metamirror can further enhance the CPERs to 14 based on the double polarization selection provided by the chiral metamirror and the detection material [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 8c, Deng et al proposed an absorption‐enhanced all‐semiconductor plasmonic cavity integrated THz QWIP on the basis of previous research work. [ 119 ] In this system, both all‐semiconductor plasmonic cavity and THz QW active material can be grown by molecular beam epitaxy simultaneously. Therefore, the optimal film quality and interface conditions can be ensured, the preparation process of plasmonic cavity can be simplified, meanwhile, the ohmic loss can be reduced also.…”
Section: Light Coupling Optimization: Critical Coupling and Suppression Of Power Loss In Photonic Structuresmentioning
confidence: 99%
“…Thus, the absorptance of the QW is 13.2 times higher than that of the standard 45° facet device. [ 119 ] Light coupling optimization improves the competitive absorption of the QWs and reduces the ohmic loss to achieve higher device performance. This light coupling optimization method pays more attention to the absorption enhancement of the active material and thus the device performance It is an important way to improve the performance of infrared detectors, and worthy of more in‐depth study in the field of infrared detection.…”
Section: Light Coupling Optimization: Critical Coupling and Suppression Of Power Loss In Photonic Structuresmentioning
confidence: 99%
“…1 The essential part of this technology is polarization discriminative infrared detectors. Although considerable polarization selectivity can be achieved by integrating anisotropic photonic structures with detection materials, [2][3][4][5][6][7] the fabrication of these composite structures is sophisticated and costly. Recently, the emergence of low-symmetry layered materials has stimulated tremendous research interest in polarization detection based on their in-plane anisotropic optical and electrical properties.…”
Section: Introductionmentioning
confidence: 99%